2010
DOI: 10.1038/cdd.2010.160
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-stimulated gene ISG12b2 is localized to the inner mitochondrial membrane and mediates virus-induced cell death

Abstract: Interferons (IFNs) are crucial for host defence against viruses. Many IFN-stimulated genes (ISGs) induced by viral infection exert antiviral effects. Microarray analysis of gene expression induced in liver tissues of mice on dengue virus (DENV) infection has led to identification of the ISG gene ISG12b2. ISG12b2 is also dramatically induced on DENV infection of Hepa 1-6 cells (mouse hepatoma cell line). Here, we performed biochemical and functional analyses of ISG12b2. We demonstrate that ISG12b2 is an inner m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…rather, it acts by inducing IFN-stimulated genes, which establish a non-virus-specific antiviral state within the cell (Lu & Liao 2011). Pawlotsky et al (2004) reassessed the effects of rBV monotherapy on early viral kinetics and found that rBV led to a small, early and transient reduction in HCV viraemia in a proportion of patients.…”
mentioning
confidence: 99%
“…rather, it acts by inducing IFN-stimulated genes, which establish a non-virus-specific antiviral state within the cell (Lu & Liao 2011). Pawlotsky et al (2004) reassessed the effects of rBV monotherapy on early viral kinetics and found that rBV led to a small, early and transient reduction in HCV viraemia in a proportion of patients.…”
mentioning
confidence: 99%
“…Ifi27l2b, is an interferon stimulated gene and its overexpression has induced apoptosis in a mouse tumour cell line (215). Hepatic Ifi27l2b gene expression was found significantly increased in Hfe -/-mice fed a HCD and consistent with the results of gene expression studies, an increase in IFI27L2B protein was also observed in these livers (Fig 4.7 A).…”
Section: Increased Expression Of Ifi27l2b Does Not Correspond To Incrsupporting
confidence: 77%
“…Ifi27l2b encodes a hydrophobic protein that is located on the inner mitochondrial membrane and overexpression of Ifi27l2b has led to mitochondrial membrane depolarisation, release of cytochrome C and subsequent mitochondria mediated apoptosis (215). Increased expression of Ifi27l2b has been observed in response to stimulation with IFNα and a toll like receptor stimulant (poly I:C) and overexpression has led to caspase-dependent cell death (215). The human equivalent of this gene IFI27 was found strongly induced by IFNα and poly I:C, and had 3-17 fold higher expression in primary human keratinocytes on treatment with TNFα, IFNγ and TGFβ1 (227,228).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than autoantibody-induced cell death, several studies have focused on the apoptosis that is directly induced by DENV infections (52)(53)(54). Studies have demonstrated that DENV infections elicit proapoptotic responses involving the suppression of Bcl-2 and Bcl-x L as well as the induction of Bax (40)(41)(42). The induction of TRAIL has been reported in human endothelial-like ECV304 cells following DENV infection (55).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Bcl-2 family members, Bax and Bcl-x L , which previous studies have shown to be involved in the DENV-mediated regulation of cell death (40)(41)(42)(43), were analyzed for comparison. RT-PCR analysis revealed that the mRNA expression levels of the proapoptotic TRAIL-R1 (DR4) and Bax were upregulated after subcytotoxic DENV challenge (Supplemental Fig.…”
Section: Denv-challenged Endothelial Cells Are Highly Sensitive To Anmentioning
confidence: 99%